Total Aortic Arch Replacement: Indications and Technical Considerations of Surgical Management - Kulyk, L.; Protsyk, I.; Beshley, D.; Schnaidruk, A.; Petsentii, V.; Babych, A. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The total aortic arch replacement is one of the most technically demanding operations, the main risk of which is the intraoperative ischemic lesion of the brain. Despite progress, operating mortality associated with this operation, even at the most renowned specialized centers reaches 7.3%. An alternative to the classic “open” operation is aortic endoprosthesis, combined with the procedure of debranching. This approach allows diminishing trauma by reducing the duration of the cardiopulmonary bypass. The aim. To describe the rational approach for replacing the total aortic arch depending on the diameter of aneurysm, the condition of the arch vessels, and the acuteness of clinical condition. The main indications for the replacement of the aortic arch are the true atherosclerotic aneurysms, genetic connective tissue diseases (Marfan syndrome), syphilis. The total arch replacement recently becomes more frequent indication for acute type A aortic dissection. The newly introduced strategies of operation and perfusion for total aortic arch replacement are aimed to reduce the risk of neurological complications. This method is named “arch first technique” which gradually replaces the earlier technique, at which the first anastomosis is performed with a descending thoracic aorta. A more traditional method called the “descending aorta first” was selected. A mandatory element of both types of the operation is antegrade cerebral perfusion. The main advantage of this method is maintaining constant perfusion of the brain which significantly reduces the risk of its ischemic damage, avoids deep hypothermia and its negative impact on blood coagulation system. The technique of total arch replacement consists of the following elements: access, double arterial cannulation, the method of brain protection, formation of distal anastomosis with descending thoracic aorta, implantation of arch vessels into the prosthesis. Sequence of anastomosis depends on morphological and clinical peculiarities of the specific case. Changes in the strategy for “open” total aortic arch replacement in various aortic pathologies is discussed based on the author’s clinical experience and literature data. Conclusions. Total aortic arch replacement remains a traumatic and technically demanding operation, the main risks of which are hemorrhage and ischemic brain lesions. The method of arch replacement – “descending aorta first” includes double arterial cannulation, antegrade cerebral perfusion, deep hypothermia with complete blood flow stoppage for the lower half of the body and the use of multi-branch vascular prosthesis.